Turbulent Bose-Einstein condensates as an out-of-equilibrium quantum systems - Orozco, Arnol Daniel Garcia (2023)
The study of quantum systems out of thermal equilibrium is currently a topic of great interest and constitutes one of the frontiers of knowledge. Bose-Einstein condensate is considered a fundamental quantum system in this context. In this thesis, the Bose-Einstein condensate of 87Rb is used to study an out-of-equilibrium system that is reached using mechanics excitations. The turbulent state is achieved through these excitations in the magnetic trap that confines the cloud. The characterization of the system is made through the momentum distribution obtained by absorption image technique in time of flight. Physical quantities such as energy flux, entropy, and length scale were calculated to help characterize the turbulence state, which is generally characterized by the appearance of a power-law in momentum distribution. The energy flux is constant within the inertial region, where the power-law appears, which is the initial indication of turbulence in the system. The entropy per particle increases rapidly when the system achieves the turbulence state, and the scale length shows the evolution of the establishment of the quantum turbulence regimen. Another topic investigated is the so-called non-thermal fixed points. In these points, where the system remains out of equilibrium but evolves according to certain special laws of scale, the system can be said to belong to a particular universality class. A single function describes the dynamics post excitation due to nearby non-thermal fixed points characterized by two exponents, which allows predicting the temporal evolution of the momentum distribution. This class of phenomena opens up new research possibilities in the quantum world out of thermal equilibrium.